Field notes and letter to Thomas H. Kent contributed by Pam Allen and Reid I. Allen, December 2, 1998 - Allen, Pamet al; Allen, Reid I.et al (1998)
Fall report of birds contributed by Pam Allen and Reid I. Allen. Also included is a letter from Pam Allen to Thomas H. Kent regarding the fall field reports. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed